The impact of the euro on international stability and volatility - Gerlach, Stefan; Hoffmann, Mathias; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2008)
We investigate the impact of EMU on macroeconomic volatility. The volatilities of inflation and nominal interest rates have declined, as has, more importantly, the volatility of real consumption growth. Since global volatility has fallen for reasons unrelated to EMU (the "great moderation"), we focus on the volatilities of bilateral differences in growth rates (or changes). Pairs of EMU countries have experienced the greatest fall in consumption volatility, followed by pairs in which one country is an EMU member. We demonstrate that these findings are closely linked to changes in consumption risk sharing. Overall, EMU has made a difference.
Economic Papers